Measuring perceived stress and burnout level among undergraduates during ODL sessions in UiTM Tapah - Mohd Isa, Noor Saatila; Mansor, Norul Akma; Zamri, Norhayati; Ab Rahman, Liyana (UiTM Cawangan Johor, 2021)
The Covid-19 pandemic has impacted nearly every industry including educational institutions. The change from traditional learning to online learning methods has created a new learning environment. Students need to adjust to a new norm of attending online lectures, connecting with lecturers and classmates virtually, and chasing dead lines for submitting work while also scheduling time for self-revision. This situation can create another issue for students which are stress and burnout during Open and Distance Learning (ODL) sessions. Hence, the purpose of the study is (1) to assess the level of perceived stress and burnout among accounting students during ODL sessions; and (2) to determine the relationship between accounting students' perceived stress and burnout during ODL sessions. An e-survey was used to deliver a set of questionnaires to accounting students on their perceived stress and burnout experiences, with a total of 314 respondents in the final sample. Perceived Stress Scale and Maslach Burnout Inventory Student Survey (NM-SS) were used to measure the perceived stress and burnout respectively. According to the findings, in terms of student burnout, 50 percent of the respondents had burnout from never to practically every week, while the other 50 percent experienced burnout from every week to even day. In terms of perceived stress, the results showed that 50 percent of the respondents felt from never to sometimes for specific perceived stress identified, while the other 50 percent felt from sometimes to very often. A substantial positive association between perceived stress and burnout was found, implying that the higher the perceived stress, the more burnout the students will feel during ODL sessions.